Components of TOR and MAP kinase signaling control chemotropism and pathogenicity in the fungal pathogen Verticillium dahliae - Vangalis, Vasileios; Markakis, Emmanouil A.; Knop, Michael; Pietro, Antonio Di; Typas, Milton A.; Papaioannou, Ioannis A. (Microbiological research, 2023)
Filamentous fungi can sense useful resources and hazards in their environment and direct growth of their hyphae accordingly. Chemotropism ensures access to nutrients, contact with other individuals (e.g., for mating), and interaction with hosts in the case of pathogens. Previous studies have revealed a complex chemotropic sensing landscape during host-pathogen interactions, but the underlying molecular machinery remains poorly characterized. Here we studied mechanisms controlling directed hyphal growth of the important plant-pathogenic fungus Verticillium dahliae towards different chemoattractants. We found that the homologs of the Rag GTPase Gtr1 and the GTPase-activating protein Tsc2, an activator and a repressor of the TOR kinase respectively, play important roles in hyphal chemotropism towards nutrients, plant-derived signals, and heterologous α-pheromone of Fusarium oxysporum. Furthermore, important roles of these regulators were identified in fungal development and pathogenicity. We also found that the mitogen-activated protein kinase (MAPK) Fus3 is required for chemotropism towards nutrients, while the G protein-coupled receptor (GPCR) Ste2 and the MAPK Slt2 control chemosensing of plant-derived signals and α-pheromone. Our study establishes V. dahliae as a suitable model system for the analysis of fungal chemotropism and discovers new components of chemotropic signaling during growth and host-pathogen interactions of V. dahliae.
Online verfügbar 12. März 2023, Artikelversion 13. März 2023
Gesehen am 25.04.2023